Reversible effect of phytohaemagglutinin on the growth and metabolism of rat gastrointestinal tract. Issue 3 (September 1995) - Bardocz, S; Grant, G; Ewen, S W; Duguid, T J; Brown, D S; Englyst, K; Pusztai, A
Abstract : The lectin, phytohaemagglutinin, present in beans survives passage through the gastrointestinal tract in a biologically and immunologically intact form. It is known that by binding to the brush border membranes of the small intestine phytohaemagglutinin induces its hyperplastic growth. However, its effect on the other parts of the gut are not known. This study considered the dose and time dependent changes in the gastrointestinal tract exposed to phytohaemagglutinin. Lectin binding was detected by polyclonal antibodies using PAP staining to the surface and the parietal cell region of the stomach, the brush border epithelium of the small intestine and to the surface membrane of the caecum and colon. To characterise the metabolic changes in the gut organ weights, protein, RNA, DNA, and polyamine contents were measured. While phytohaemagglutinin induced a dose and time dependent growth of the small intestine by lengthening the tissue and thickening the gut wall by increasing the number of crypt cells, the lectin also changed the size and metabolism of the large intestine and pancreas, but this growth was by hypertrophy. Phytohaemagglutinin in the diet influences the size, metabolism, and function of the entire digestive tract. The lectin induced changes were fully or partially reversed within three days.